Advancing Melanoma Care: Microneedles for Diagnosis and Therapeutic Precision - Chauhan, Shreyansh; Naik, Jai; Vinchhi, Preksha; Patel, Mayur M. (Current Pharmaceutical Design, 2025)
Melanoma, an aggressive skin tumor derived from melanocytes, is associated with a high mortality rate attributed to its frequent metastasis, drug resistance, and high invasion rate. The current therapeutic interventions for melanoma, such as surgery, chemotherapy, immunotherapy, and radiation therapy, are not efficient enough to treat melanoma. The current melanoma care is associated with limitations, such as late diagnosis and staging, false positives, treatment resistance, immune-related side effects, lack of standardization, challenges in metastatic melanoma cure, high treatment costs, recurrence, etc. Conventional therapies have poor anti-cancer efficacy due to premature drug degradation, severe adverse effects owing to systemic drug exposure, and low drug concentration at the malignancy site. Moreover, the current diagnosis for melanoma is associated with painful sample collection techniques, limited imaging techniques, limited understanding of genetic markers, etc., leading to misdiagnosis or delayed diagnosis. An extensive literature review on Microneedles (MNs) for melanoma diagnosis and treatment was conducted using PubMed, ScienceDirect, and Google Scholar databases from 2012 to 2025. This mini-review presents the advantages of MNs over current therapy, their formulation aspects, and their advancements for the diagnosis and treatment of melanoma. MNs, an emerging drug delivery system, can efficiently penetrate the skin barriers and form reversible microchannels to deliver the drug at melanoma sites without drug leakage, mitigating the adverse effects and increasing drug accumulation. MNs also provide an excellent platform to integrate novel and conventional therapies by encompassing discrete therapeutic agents in a single matrix. Moreover, MNs can capture biomarkers by absorbing the skin Interstitial Fluid (ISF) and facilitate diagnosis by minimal biological samples.
Keywords: controlled release